A way to the engineering of the quantum states of trapped ions – report of work in progress - Stachowska, Ewa; Szawioła, Gustaw; Buczek, Adam; Koczorowski, Wojciech; Furmann, Bogusław; Krzykowski, Andrzej; Stefańska, Danuta; Walaszczyk, Adrian; Jarosz, Andrzej; Dembczyński, Jerzy (Oficyna Wydawnicza Politechniki Wrocławskiej, 2006)
We studied the influence of geometry on the interaction of ions in a Paul trap with microwave radiation and the spatial velocity distribution from the Doppler shift. Non-linear resonances in a Paul trap for Pr+ ions were observed.
Optica Applicata, Vol. 36, 2006, nr 4, s. 581-586
Keywords: optyka; Paul trap; nonlinear resonances; double optical-rf resonance technique